2015
DOI: 10.1093/jrr/rrv083
|View full text |Cite
|
Sign up to set email alerts
|

Reirradiation of spinal metastases with intensity-modulated radiation therapy: an analysis of 23 patients

Abstract: This study aimed to evaluate the efficacy and safety of reirradiation with intensity-modulated radiation therapy (IMRT) for spinal metastases. We retrospectively analyzed 23 patients with spinal metastases who underwent IMRT reirradiation between December 2006 and July 2013. We evaluated the spinal radiation doses during the first and second radiation therapy courses, the interval between the courses, and the clinical outcomes after reirradiation, including skeletal-related events, local control rates (LCRs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…High-quality pain response data unfortunately is limited within the literature in this population of patients; however, published series suggest overall response rates of 65% to 79%. 61 64 …”
Section: Spine Sbrt Treatment Outcomesmentioning
confidence: 99%
“…High-quality pain response data unfortunately is limited within the literature in this population of patients; however, published series suggest overall response rates of 65% to 79%. 61 64 …”
Section: Spine Sbrt Treatment Outcomesmentioning
confidence: 99%
“…This distinction may be useful in the irradiation of spine or pelvic bone metastases, particularly for Re-RT. Kawashiro et al ( 11 ) reported clinical IMRT results of Re-RT for spinal metastasis. They concluded that spinal metastasis Re-RT using IMRT was safe and that pain relief and paresis improvement and/or prevention may be expected along with a reduced risk of radiation-induced toxicity, especially in the spinal cord ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kawashiro et al ( 11 ) reported clinical IMRT results of Re-RT for spinal metastasis. They concluded that spinal metastasis Re-RT using IMRT was safe and that pain relief and paresis improvement and/or prevention may be expected along with a reduced risk of radiation-induced toxicity, especially in the spinal cord ( 11 ). In addition, Jereczek-Fossa et al ( 12 ) reported that the low toxicity of Re-RT with IMRT or SBRT should allow for delivery of higher doses and lead to improvement in Re-RT outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SABR is the only option for repeat radiation. The results (13,17,(34)(35)(36)(37)(38)(39) demonstrated that repeat SABR achieved good efficacy in controlling tumor-related pain (Table 2).…”
Section: Sabr Treatment After Prior Radiotherapymentioning
confidence: 93%